Concepções de surdez: A visão do surdo que se comunica em língua de sinais - Lopes, Mara Aparecida de Castilho [UNESP]; Leite, Lúcia Pereira [UNESP] (FapUNIFESP (SciELO), 2011)
At this time, diverse views on deafness are present in society. Such views, in general, arecharacterized by theoretical disputes between communicative possibilities - either oral or gestural - based onthe importance of having appropriated oneself of a language code for the development of language, which isessential in the constitution of subjectivity of human beings. Thus, this study aimed to identify the conceptionsof deaf people had about their condition. To collect the data we used semi-structured interviews, applied toten participants who were deaf adult users of the Brazilian Sign Language - Libras. The interviews were taped,transcribed and subjected to content analysis. The results indicate that the conceptions of deafness constitute amultifaceted view on this condition, infl uenced by social relations throughout each person's life trajectories. Theresearchers perceived that learning Libras enabled deaf persons to constitute their own assertiveness as someonewho is different, with different needs.
Conceptions of deafness: The vision of the deaf person who communicates in sign language
Keywords: Deafness; Language; Social interaction; Special education